Service Innovation at the Regional Revenue Agency of Maluku Province In Increasing Local Revenue - Suwija Patta; Wahab Tuanaya; Normawati Normawati; Safrudin Bustam Layn (Journal of Government Science Studies, 2026)
This study aims to analyze and explain the Service Innovation at the Regional Revenue Agency of Maluku Province in Increasing Local Revenue. Using in-depth interview data collection techniques with the help of an interview guide. In addition, direct document tracing was conducted while observing, reading, and understanding concepts, to obtain secondary data from work reports, legislation, regional regulations, decrees, and brochures related to the issues faced. The data from this research were analyzed using descriptive qualitative analysis techniques. The research results show that, 1) The Maluku Provincial Bapenda enhances the capacity of ASN human resources, which can support public service innovations, thereby impacting the increase in PAD. 2) The Maluku Provincial Bapenda innovates services to the community thru the digitalization of tax and retribution payments based on online systems, which can increase the community's enthusiasm for paying taxes and retributions, thereby increasing PAD. 3) The Maluku Provincial Bapenda innovates services thru the development of PAD sources, including intensification and extensification, which impacts the increase in PAD. 4) The Maluku Provincial Bapenda innovates services to the community by simplifying the service process, which impacts the increase in the community's willingness to pay taxes and retributions, thereby contributing to the increase in PAD.